What interventions and programmes are available to support older nurses in the workplace? A literature review of available evidence. (March 2023) - Montayre, Jed; Knaggs, Gilbert; Harris, Celia; Li, Weicong; Tang, Liyaning (Maggie); de Almeida Neto, Abílio; Antoniou, Mark
Abstract: Background: High exit rates, stalling entry rates, population ageing, and, most recently, the COVID-19 pandemic have placed significant strain on the world's nursing workforce. Both developed and developing countries face similar predicaments. Evidence-based programmes to support older nurses in the workplace are urgently needed to ensure the sustainability of a career in nursing for this group of healthcare professionals. Objectives: To scope and synthesise available evidence on evaluated programmes and interventions implemented to support the ageing nursing workforce's health, wellbeing, and retention. Design: A literature review of available evidence using a systematic approach. Method: Medline, Scopus, PsycINFO and CINAHL were searched for relevant peer-reviewed evidence. Data from the peer-reviewed literature were extracted separately into purpose designed-extraction spreadsheets. Information relevant to study design, intervention design, outcome constructs, intervention outcomes, and barriers and enablers to intervention success were collected. The protocol for this review was registered in PROSPERO [CRD42021274491]. Results: Eighteen published studies were included in this review. We identified a range of interventions and programmes that have been implemented to support older nurses, which included flexible and reduced work arrangements, mentoring programmes, exercise and lifestyle interventions, continued professional development and purpose-designed remote retreats. We found limited evidence of evaluated outcomes from workplace support interventions that addresses the actual challenges faced by ageing nurses as reported in previous literature reviews. Interventions that were designed to promote a sense of purpose at work resulted in positive outcomes and appeared to more directly address the stated needs of older nurses. Holistic programmes and interventions that could potentially promote both physical well-being and psychological well-being required a broader, whole-of-organisation approach rather than more piecemeal interventions addressing individual physical and mental health concerns. Interventions which acknowledged older nurses' clinical expertise and experience (e.g., mentoring programmes) were linked to positive outcomes. Conclusion: Future intervention efforts should acknowledge and balance intervention participation opportunities against existing everyday workload constraints faced by older nurses. Our review suggests the need for further intervention studies assessing specific outcomes such as psychological and emotional health, as well as interventions that more directly address the most pressing concerns that ageing nurses report at personal and organisational levels. A paradigm shift in productivity measurement in clinical nursing work is required in order to increase the value placed on the unique contribution of older nurses working clinically, particularly in sharing their acquired knowledge, skill, and expertise.